Effectiveness of different irrigation protocols on calcium hydroxide removal from simulated immature teeth after apexification - Evren Ok; Mustafa Altunsoy; Mehmet Tanriver; İsmail Davut Çapar (Medical Journals Sweden, 2015)
Aim: To evaluate the effectiveness of different irrigation solutions and ultrasonic activation of the irrigation solutions on the removal of calcium hydroxide (Ca(OH)2) from the simulated immature root canals after apexification. Materials and methods: One-hundred and one single-rooted teeth were used. The root canals were shaped with ProTaper rotary files up to F5. Simulation of roots with immature apices was carried out using size 4 Unicore drills. An injectable Ca(OH)2 was injected into each root canal, and packed to the working length. Then, cotton pellets were placed over canal orifices, and apical and coronal parts of the roots were sealed with resin-modified glass ionomer cement, and light cured. Specimens were stored in distilled water for 3 months at 37°C. After 3 months, the temporary coronal seal was removed and the samples were randomly divided into: (a) saline (n = 20), (b) ultrasonic activation of saline (n = 20), (c) sodium hypochlorite (NaOCl) (n = 20), (d) ultrasonic activation of NaOCl (n = 15), (e) chlorhexidine digluconate (CHX) (n = 20) and one positive control group (n = 3) and one negative control group (n = 3). The amount of remaining Ca(OH)2 on the canal walls was measured under stereomicroscope with 30× magnification. Comparisons between groups were made by the non-parametric Kruskal-Wallis test and Dunn post-test at a significance level of p < 0.05. Results: There were no significant differences among the saline, ultrasonic activation of saline, NaOCl, ultrasonic activation of NaOCl and CHX (p > 0.05) groups. Conclusions: Irrigation solutions and ultrasonic activation of the irrigation solutions could not completely remove Ca(OH)2 from the simulated immature root canals.